The Effect Of Using Animated Videos on A2 Level Writing Skills Of Grade Students XII - Jesica Valencia Hutabalian; Yanti Arasi Sidabutar; Tarida Alvina Simanjuntak (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This research aims to investigate the effect of using animated videos on the A2 level writing skills of Grade XII students at SMA Swasta Nommensen Pematangsiantar Campus. This research applied a quantitative method with a Pre-Experimental design, specifically the One Group Pretest-Posttest Design. The research instrument was an essay test consisting of one item. After conducting data analysis, the mean score of the pretest was 63, while the mean score of the posttest was 83.4. The sample consisted of 23 students from Grade XII. Based on the hypothesis testing using the T-test and N-Gain test, the analysis showed that the t-observed value was 12.972, while the t-table value with a degree of freedom (df) of 22 at a significance level of 0.05 was 1.717. Since t-observed > t-table (12.972 > 1.717), the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. Furthermore, the N-Gain score percentage was 55.4%. Therefore, it can be concluded that the use of animated videos has a significant effect on improving the A2 level writing skills of Grade XII students at SMA Swasta Nommensen Pematangsiantar Campus